Área de proteção ambiental da Ilha do Combu, Belém/PA: desafios de implantação e de gestão de uma unidade de conservação - RIBEIRO, Jocilete de Almeida (Universidade Federal do Pará, 2012)
This dissertation consists in a case study of the creation, implementation and management of the Environmental Protection Area of the Island of Combu (Combu EPA) located in the city of Belem in Para state, temporally bounded from the act of its creation in 1997 to the current period, 2010. As main objectives it was intended to analyze and reflect on the key challenges and possibilities for environmental management of the Environmental Protection Area of the Island of Combu, identifying the main changes in the Island of Combu after the process of creation of the EPA, and to identify existing problems the EPA Island Combu. The problems we intend to answer are: What are the major challenges and possibilities for environmental management in the EPA Island Combu in the current context? How was the process of creation of the EPA Island Combu in the point of view of managing agency and the local leaders? What have the creation of the EPA meant for the population of the Island of Combu from the perspective of local leaders? The research is qualitative and interdisciplinary since it approaches the problem from the point of view of several disciplines seeking a holistic view. For its implementation was conducted a literature review, consultation and analysis of documentary sources, field trips, trails on the island, simple observation in meetings and workshops and interviews with local leaders of the EPA, managers and technicians of the environmental agency. We make use of cartography as a methodological resource to understand the dynamics of that territory and to make a georeference of the current configuration of the EPA by GPS. The main conclusions point to the weakness of management in protected areas. The challenges refer to aspects related to the demands, the cultural aspect, the managing agency and counsel and an attentive vision. The possibilities are found in the maintenance of a well preserved forest, the existence of a significant institutional arrangement and leaders committed to the place. The creation of the EPA was not started by the local population and there was not an understanding by all about its creation. The creation of the EPA did not have much meaning to people’s daily activities, because no change was perceived since its creation. However, it points out that from two years now it is already noticed some slight tentative by the agency in charge, even with great expectation in the building of EPA head office on the island.